The Determinants of Frauds in Local Governments (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
AbstractCorruption continues to be pervasive throughout Indonesia. An ICW report in 2019 states that a total of 580 corruption suspects have been brought to trial. Civil servants were the main perpetrators of corruption, followed by municipal heads and local legislative heads and members. Perpetrators commit corruption mostly through budget misuse, mark-ups, fictitious reports, and embezzlement. Corruption is a serious problem because it is committed by the highest-ranking officers in organizations. The data confirms the importance of research on fraud in Indonesian local governments. In this respect, this study seeks to test the effectiveness of fraud diamond theory (pressure, opportunity, rationalization, and capability) in detecting fraud in Indonesian local governments. Our population is local governments in Java island. This study uses cross-sectional data obtained from local government corruption cases in Java Island during the 2015-2018 period that were legally resolved with binding Supreme Court decisions (inkracht). The results empirically find that performance accountability, regional autonomy, capital expenditure, fiscal decentralization, and mayoral tenure affect fraud in Indonesian local governments.Â Keywords: corruption; local governments; fraud diamond theory